Introduction to Functions
Introduction to Functions
input output
function
More precisely, a rule is a function if it produces only a single output for any given input. The
function with the rule ‘treble the input’ is shown in Figure 2.
f f
input treb he input
le t output
4 Treble the input 12
4 12
f
x 3x
x Treble the input 3x
Note that with an input of 4 the function will produce an output of 12. With a more general input,
x say, the output will be 3x. It is usual to assign a letter or other symbol to a function in order to
label it. The trebling function in Figure 2 has been given the symbol f .
Key Point 1
A function is a rule which operates on an input
and produces a single output from that input.
HELM (2015): 3
Section 2.1: Basic Concepts of Functions
Tas k
Write down the output from the function shown in Figure 3 when the input is
(a) 4, (b) 3, (c) x (d) t.
function
Figure 3
Your solution
In each case the function rule instructs you to multiply the input by 7 and then subtract 2. Evaluate
the corresponding outputs.
Answer
(a) When the input is 4 the output is 26
(b) When the input is 3 the output is 23
(c) When the input is x the output is 7x 2
(d) When the input is t the output is 7t 2.
Several di↵erent notations are used by engineers to describe functions. For the trebling function in
Figure 2 it is common to write
f (x) = 3x
This indicates that with an input x, the function, f , produces an output of 3x. The input to the
function is placed in the brackets after the ‘f ’. f (x) is read as ‘f is a function of x’, or simply ‘f of
x’, meaning that the value of the output from the function depends upon the value of the input x.
The value of the output is often called the ‘value of the function’.
4 HELM (2015):
Workbook 2: Basic Functions
®
Example 1
State in words the rule defined by each of the following functions:
(a) f (x) = 6x
(b) f (t) = 6t 1
(c) g(x) = x2 7
(d) h(t) = t3 + 5
(e) p(x) = x3 + 5
Solution
(a) The rule for f is ‘multiply the input by 6’.
(b) Here the input has been labelled t. The rule for f is ‘multiply the input by 6 and subtract 1’.
(c) Here the function has been labelled g. The rule for g is ‘square the input and subtract 7’.
(d) The rule for h is ‘cube the input and add 5’.
(e) The rule for p is ‘cube the input and add 5’.
Note from Example 1, parts (d) and (e), that it is the rule that is important when describing a
function and not the letters used. Both h(t) and p(x) instruct us to ‘cube the input and add 5’.
Tas k
Write down a mathematical function which can be used to describe the following
rules:
(a) ‘square the input and divide the result by 2’. Use the letter x for input and
the letter f to represent the function.
(b) ‘divide the input by 3 and add 7’. Call the function g and call the input t.
Your solution
Answer
x2 t
(a) f (x) = , (b) g(t) = + 7
2 3
Exercise
State the rule of each of the following functions:
(a) f (x) = 5x, (b) f (t) = 5t, (c) f (x) = 8x + 10, (d) f (t) = 7t 27, (e) f (t) = 1 t,
t 2 1
(f) h(t) = + , (g) f (x) =
3 3 1+x
HELM (2015): 5
Section 2.1: Basic Concepts of Functions
Answers
(a) multiply the input by 5. (b) same as (a). (c) multiply the input by 8 and then add 10. (d)
multiply the input by 7 and then subtract 27. (e) subtract the input from 1. (f) divide the input
by 3 and then add 2/3. (g) add 1 to the input and then find the reciprocal of the result.
Example 2
Given the function f (x) = 3x + 1 find
(a) f (2)
(b) f ( 1)
(c) f (6)
Solution
(a) The output from the function needs to be found when the argument or input is 2. We
need to replace x by 2 in the expression for the function. We find
f (2) = 3 ⇥ 2 + 1 = 7
(b) Here the argument is 1. We find
f ( 1) = 3 ⇥ ( 1) + 1 = 2
(c) f (6) = 3 ⇥ 6 + 1 = 19.
Tas k
Given the function g(t) = 6t + 4 find (a) g(3), (b) g(6), (c) g( 2)
Your solution
Answer
a) g(3) = 6 ⇥ 3 + 4 = 22, (b) g(6) = 40, (c) g( 2) = 8
6 HELM (2015):
Workbook 2: Basic Functions
®
It is possible to obtain the value of a function when the argument is an algebraic expression. Consider
the following Example.
Example 3
Given the function y(x) = 3x + 2 find
(a) y(t)
(b) y(2t)
(c) y(z + 2)
(d) y(5x)
Solution
The rule for this function is ‘multiply the input by 3 and then add 2’. We can apply this rule
whatever the argument.
(a) In this case the argument is t. Multiplying this by 3 and adding 2 we find y(t) = 3t + 2.
Equivalently we can replace x by t in the expression for the function, so, y(t) = 3t + 2.
(b) In this case the argument is 2t. We need to replace x by 2t in the expression for the
function. So y(2t) = 3(2t) + 2 = 6t + 2
(c) In this case the argument is z + 2. We find y(z + 2) = 3(z + 2) + 2 = 3z + 8. It is
important to note that y(z + 2) is not y ⇥ (z + 2) = yz + y2 but instead reads ‘y of
(z + 2)’ where ‘of’ means ‘take the function of’.
(d) Here we have a complication. The argument is 5x and so there appears to be a clash
of notation with the original expression for the function. There is no problem if we
remember that the rule is to multiply the input by 3 and then add 2. The input now is
5x. So y(5x) = 3(5x) + 2 = 15x + 2.
Tas k
Given the function g(x) = 8 2x find (a) g(4), (b) g(4t), (c) g(2x 3)
Your solution
(a)
(b)
(c)
HELM (2015): 7
Section 2.1: Basic Concepts of Functions
Answer
(a) g(4) = 8 2⇥4=0
(b) g(4t) = 8 2 ⇥ 4t = 8 8t
(c) g(2x 3) = 8 2(2x 3) = 14 4x
Exercises
1. Explain what is meant by the ‘argument’ of a function.
2. Given the function g(t) = 8t + 3 find (a) g(7), (b) g(2), (c) g( 0.5), (d) g( 0.11)
3. Given the function f (t) = 2t2 + 4 find: (a) f (x) (b) f (2x) (c) f ( x) (d) f (4x + 2)
t
(e) f (3t + 5) (f) f ( ) (g) f (t ) (h) f ( )
↵
4. Given g(x) = 3x2 7 find (a) g(3t), (b) g(t + 5), (c) g(6t 4), (d) g(4x + 9)
1
5. Calculate f (x + h) when (a) f (x) = x2 , (b) f (x) = x3 , (c) f (x) = . In each case write
x
down the corresponding expression for f (x + h) f (x).
1 x
6. If f (x) = find f ( ).
(1 x)2 `
Answers
3. (a) 2x2 + 4, (b) 8x2 + 4, (c) 2x2 + 4, (d) 32x2 + 32x + 12, (e) 18t2 + 60t + 54,
2 2t2
(f) 2 + 4, (g) 2(t )2 + 4, (h) + 4.
↵2
4. (a) 27t2 7, (b) 3t2 + 30t + 68, (c) 108t2 144t + 41, (d) 48x2 + 216x + 236.
1
5. (a) x2 + 2xh + h2 , (b) x3 + 3x2 h + 3xh2 + h3 , (c) .
x+h
The corresponding expressions are (a) 2xh + h2 , (b) 3x2 h + 3xh2 + h3 ,
1 1 h
(c) = .
x+h x x(x + h)
1
6. x 2.
(1 `
)
8 HELM (2015):
Workbook 2: Basic Functions
®
3. Composition of functions
Consider the two functions g(x) = x2 , and h(x) = 3x + 5. Block diagrams showing the rules for
these functions are shown in Figure 4.
h
treble the input 3x + 5
x and add 5
Suppose we place these Block diagrams together in series as shown in Figure 5, so that the output
from function g is used as the input to function h.
g h
x2 treble the input
x square the input
and add 5 3x2 + 5
Study Figure 5 carefully and deduce that when the input to g is x the output from the two functions
in series is 3x2 + 5. Since the output from g is used as input to h we write
h(g(x)) = h(x2 ) = 3x2 + 5
The form h(g(x)) is known as the composition of the functions g and h.
Suppose we interchange the two functions so that h is applied first as shown in Figure 6.
h g
treble the input
x and add 5 square the input (3x + 5)2
Study Figure 6 and note that when the input to h is x the final output is (3x + 5)2 . We write
g(h(x)) = (3x + 5)2
Note that the function h(g(x)) is di↵erent from g(h(x)).
HELM (2015): 9
Section 2.1: Basic Concepts of Functions
Example 4
Given two functions g(t) = 3t + 2 and h(t) = t + 3 obtain an expression for the
composition g(h(t)).
Solution
We have g(h(t)) = g(t + 3). Now the rule for g is ‘triple the input and add 2’, and so we can
write g(t + 3) = 3(t + 3) + 2 = 3t + 11 so, g(h(t)) = 3t + 11.
Tas k
Given the two functions g(t) = 3t + 2 and h(t) = t + 3 as in Example 4 above,
obtain an expression for the composition h(g(t)).
Your solution
We have
h(g(t)) = h(3t + 2)
State the rule for h and write down h(g(t)).
Answer
‘add 3 to the input’, h(3t + 2) = 3t + 5. Note that h(g(t)) 6= g(h(t)).
Exercises
1. Find f (g(x)) when f (x) = x 7 and g(x) = x2 .
2. If f (x) = 8x + 2 find f (f (x)).
3. If f (x) = x + 6 and g(x) = x2 5 find (a) f (g(0)), (b) g(f (0)), (c) g(g(2)), (d) f (g(7)).
x 3 1
4. If f (x) = and g(x) = find g(f (x)).
x+1 x
Answers
1. x2 7.
10 HELM (2015):
Workbook 2: Basic Functions